Improving the effectiveness of the implementation of anti-corruption strategy through the improvement of the Criminal Code of the Republic of Kazakhstan - Mitskaya, E.V. (Bulletin of the Karaganda University “Law Series”, 2022)
Based on the comparative-legal method, interpreting criminal law norms, considering the doctrine of Kazakh criminal law, this study pays attention to the science-based nature of implementing international standards of combating corruption in national criminal law to develop proposals to strengthen liability for corruption of-fenses. Implementation of some recommendations of the 4th round of monitoring of the Istanbul Anti-Corruption Action Plan is fraught with application problems of criminal law norms as they contradict the doc-trine of Kazakh criminal law. To strengthen liability for corruption offenses, set out in the new Concept of an-ti-corruption policy of Kazakhstan, the author proposes to implement only those norms of international stand-ards of combating corruption, which does not contradict the doctrine of Kazakhstani criminal law. It is neces-sary to eliminate the restrictive understanding of the subject of bribery only by property benefits, expand the public official’s understanding, enshrine unjustified enrichment, thereby eliminating the limited spread of the repressive power of criminal law on manifestations of corruption. Besides, the author suggests using the in-ternal resource of criminal law to combat corruption. Appropriate proposals are made to adjust the Criminal Code of Kazakhstan, including the elimination of duplication of corruption offenses in the Criminal Code of Kazakhstan and the administrative law.